Hannah Arendt, the right to have rights and contemporary challenges - Wyrębska-Ðermanović, Ewa (Hybris, 2020)
The article delivers a commentary to Hannah Arendt’s 1949 essay The Rights of Man. What Are They? The author argues, that the concept of “the right to have rights”, which Arendt introduced in this early text, bears significant relevance for contemporary political situation worldwide. The subsequent parts of the article (1) present the two fundamental features of the situation of the rightless, which are brought up by Arendt, (2) describe “the right to have rights” as an insurmountable problem of modern times and (3) refer to possible solutions of the issue proposed by O. Höffe and S. Benhabib.